1 Carotid plaque lipid reduction, determined by T2 mapping, occurs early after high-intensity statin initiation in patients presented with acute myocardial infarction. (May 2018) - Alkhalil, Mohammad; Biasiolli, Luca; Akbar, Naveed; Galassi, Francesca; Chai, Joshua T; Robson, Matthew D; Choudhury, Robin P
Abstract : Introduction: A recently-validated, highly sensitive T2 mapping magnetic resonance (MRI) technique accurately quantifies carotid atherosclerotic plaque lipid. The aims of this study were to test the hypothesis that intensive LDL-c reduction translates into rapid depletion of plaque lipids and whether plaque lipid content is related to standard or 'functional' blood lipid measurements, including PCSK9 level and cholesterol efflux capacity. Methods: Statin naïve subjects presenting with acute coronary syndrome underwent carotid artery MRI at 3 Tesla scanner to quantify plaque lipid. Patients were subsequently commenced on high dose statin as part of clinical care and underwent a second MRI after three months. Plaque composition was measured using objective semi-automated techniques implemented in Matlab and statistical analysis was performed using SPSS 22.0. Results: 23 out of 24 patients had measurable lipid. Three months after statin initiation there was a significant reduction in carotid lipid percentage [from 10.3% (7.2–14.2) to 7.4% (5.4–10.0), p=0.002] and a significant increase in fibrous percentage [from 83.3%±6.6 to 85.5%±4.8, p=0.039]. None of the studied functional blood biomarkers were related to either baseline carotid plaque lipid content or its propensity to change with statin treatment. Conclusion: T2-mapping demonstrated depleted carotid plaque lipid following the initiation of high-intensity statin treatment. Standard or functional blood biomarkers did not predict changes in plaque lipid content with treatment. These findings support the use of plaque imaging as a potential tool to identify patients who may be suitable for intensive lipid modification.